Perbedaan Organizational Citizenship Behavior (OCB) Ditinjau Dari Identifikasi Organisasi Guru SD PNS dan Honorer - Zakia Nurul Fitriana; Munawir Yusuf; Fadjri Kirana Anggarini (Journal of Research and Measurement in Psychology, 2020)
This study aims to find out: (1) differences of organizational citizenship behavior in terms of organizational identification in PNS and honorary elementary school teachers (2) differences of organizational citizenship behavior in terms of organizational identification (3) differences of organizational citizenship behavior in PNS and honorary elementary school teachers. The population was elementary school teachers in Wonosari Subdistrict, using cluster random sampling, a minimum sample of Slovin preliminaries was received by 174 teachers. With a sample of 87 honorary and 89 PNS teachers, uses citizenship organizational behavior (α = 0.907) and organizational identification scale (α = 0.854). With two-way Anova hypothesis test, it was found that there was no difference in organizational citizenship behavior in terms of organizational identification in PNS and honorary teachers (F = 0.974; p> 0.05), there were differences of organizational citizenship behavior in terms of organizational identification ​​( F = 36.768; p <0.05), and there were no differences of organizational citizenship behavior in PNS and honorary teachers (F = 0.139; p> 0.05). The results of the additional analysis prove that there is no difference of organizational citizenship behavior in terms of years of service, gender, age, and salary.